Комплексная оценка состояния полости носа и верхнечелюстных пазух после реконструктивных операций на верхней челюсти (Эндодонтия Today)
Complex research of condition cavity nose at 23 patients with bite anomales after upper jaw osteotomy are present. There are present typical types changes of caviti nose and sinus maxillaris anatomy. Recommendations by prediction and correction changes mucosa and walls are present. Deep disturbance, which could make difficult breathing, was not found.